Effectiveness of Cognitive Behavior Therapy in Enhancing Self-Esteem Among Schizophrenia Patients at Dr. Soeharto Heerdjan Psychiatric Hospital, Jakarta in 2024 - Diah Sukaesti Hendraswantoro; Lilis Komalasari; Anita Sukarno (RSUP Dr. Kariadi, 2024)
BACKGROUND : Schizophrenia patients often experience low self- esteem which requires modality therapy, one of modality therapy for the patients with mental disorders is cognitive behavioral therapy (CBT). AIMS : The aim of this research is to determine the effectiveness of cognitive behavior therapy in increasing self-esteem. and abilities in Schizophrenia patients. METHOD : This research method is quasi-experimental with one group pre-post design with control. The data was analyzed by Paired t test. The research was conducted in one hospital on 50 control patients and 50 intervention patients. RESULT : The research results showed that cognitive behavior therapy significantly reduced signs and symptoms in clients with low self-esteem (P-value ≤ 0.05 ). The comparison of self-esteem scores in the intervention group was significantly higher compared to the control group (P-value ≤ 0.05 ). CONCLUSION : Conclusions and suggestions: Cognitive behavior therapy is effective for patients with low self-esteem because it can increase self-esteem and abilities in patients with schizophrenia. Future researchers should conduct research using cognitive behavior therapy without providing psychotherapy.